1992
DOI: 10.1007/bf00202104
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric constants of topaz, orthoclase and scapolite and the oxide additivity rule

Abstract: Abstract.The dielectric constants and dissipation factors of topaz, scapolite and orthoclase were determined at i MHz using a two-terminal method and empirically determined edge corrections. The results are: The deviation (A) between measured dielectric polarizabilities as determined from the Clausius-Mosotti equation and those calculated from the sum of ion polarizabilities according to ~o(mineral)= s for topaz is 2.5%. The large deviations of orthoclase and scapolite from the oxide additivity rule with A=+7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Although the measurement of individual ǫ s,⊥ and ǫ s, components for HAp has not been reported, our values are not far from ǫ s,⊥ = 10.5 and ǫ s, = 8.7 which were observed for crystalline fluorapatite. 75 The effective medium approximated dielectric constant is estimated as ǫ s,EMA = 11, regardless the exchange-correlation functional. The experimental static dielectric constant de-termined for HAp powder samples varies widely, and strongly depends on the porosity and amount of water within the samples.…”
Section: Propertymentioning
confidence: 99%
“…Although the measurement of individual ǫ s,⊥ and ǫ s, components for HAp has not been reported, our values are not far from ǫ s,⊥ = 10.5 and ǫ s, = 8.7 which were observed for crystalline fluorapatite. 75 The effective medium approximated dielectric constant is estimated as ǫ s,EMA = 11, regardless the exchange-correlation functional. The experimental static dielectric constant de-termined for HAp powder samples varies widely, and strongly depends on the porosity and amount of water within the samples.…”
Section: Propertymentioning
confidence: 99%
“…The identification of dc conductivity provides a quantifiable explanation of the behaviour of REEs during the electrostatic separation stage [2]. Moreover, the determination of the dielectric parameters (dielectric constant and loss, polarization, relaxation time and resonance frequency) can specify this behaviour [9][10][11][12][13][14]. Accurate and precise concentrations of REEs in the samples were obtained in a previous work [15,16].…”
Section: Introductionmentioning
confidence: 94%
“…Silicates are the most abundant mineral found on the earth’s surface, especially feldspar minerals . Generally silicates, aluminosilicates, and feldspar materials are reported to have a low dielectric constant value of approximately in the range of 3–8, and hence they are extensively used in semiconductor devices, microelectronics, and integrated circuits. Various studies revealed that the dielectric constant considerably decreases with the increase in the silicate content within the structure. , Moreover, the presence of modifying cations such as K + , Na + , Mg 2+ , Ca 2+ , etc. and their consecutive migration within the structure determine the electrical properties of the aluminosilicates .…”
Section: Introductionmentioning
confidence: 99%